Restricted-magnesium-vapor-reduction of amorphous SiO/C precursors to polycrystalline Si/SiOx/C hybrid anodes. Issue 9 (10th January 2023) - Zhang, Jun; Zhang, Fan; Zhu, Wenqiang; Xi, Xiaoming; Yang, Lezhi; Tu, Feiyue; Feng, Qingge; Li, Tingting; Yang, Yahui; Yang, Lishan
Abstract : A method that combines disproportionation and magnesium-vapor-reduction in one step, which is different from traditional magnesium thermal reduction, was designed for synthesizing advanced silicon-based anode materials. Abstract : Considering the electrochemical activity/stability and preparation feasibility of silicon (Si) nanomaterials, we designed a restricted-magnesium-vapor-reduction to fabricate sustainable Si/SiO x /C porous anodes with nanopores and polycrystalline structures.